Fundamentals of biology 1 - Morano, Lourdes S.; Lopez, Crisanto S.;Tan, Andrew Eusebio S. (Quezon City, Philippines : Lorimar Publishing Company Inc., 2011)
This book is a product of PAFTE Write shop Project. Said project aims to provide the current teacher education curriculum with learning materials that comply with the Table of Specifications of the Licensure Examination for Teachers.
Module 1. Biology and You -- Module 2. Understanding Cells: The Building Pieces of Life -- Module 3. Cell Division -- Module 4. Genetics -- Module 5. Evolution -- Module 6. Introduction to Ecology -- Module 7. Diversity Among Bacteria and Viruses -- Module 8. Protists and Fungi -- Module 9. Diversity in Animals -- Module 10. The Green World: Plants.
Includes bibliographical references.
Keywords: BIOLOGY -- PLANTS